2019
DOI: 10.3390/w11061140
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Water Allocation Strategies and Conjunctive Use to Reduce Water Scarcity and Scarcity Costs for Irrigated Agriculture in Southern Brazil

Abstract: The lack of adequate management programs alongside water resources overexploitation have led to undesirable effects such as water shortages and economic losses in several regions. Optimized water allocation strategies using groundwater and surface water resources could reduce water scarcity and scarcity costs by exploring the advantages and peculiarities of each source, thus reducing the effect of variability and uncertainties on water availability. The aim of this study is to assess economic water allocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In this context, CM can be considered as an important pathway for enhancing access to irrigation and prioritizing investments because of its prospects to enhance water-use efficiency, improve water security, and ultimately result in better water productivity, along with several other benefits (e.g., flood management) ( Pandey et al, 2021 ). Furthermore, CM can effectively maximize water use benefits through augmenting supply, increasing productivity, avoiding aquifer mining, and integrating surface- and ground-water management ( Mattiuzi, Marques, and Medellín-Azuara, 2019 ).…”
Section: Context and Description Of The Case Study Area: Western Nepa...mentioning
confidence: 99%
“…In this context, CM can be considered as an important pathway for enhancing access to irrigation and prioritizing investments because of its prospects to enhance water-use efficiency, improve water security, and ultimately result in better water productivity, along with several other benefits (e.g., flood management) ( Pandey et al, 2021 ). Furthermore, CM can effectively maximize water use benefits through augmenting supply, increasing productivity, avoiding aquifer mining, and integrating surface- and ground-water management ( Mattiuzi, Marques, and Medellín-Azuara, 2019 ).…”
Section: Context and Description Of The Case Study Area: Western Nepa...mentioning
confidence: 99%
“…Os custos para se fazer a gestão de recursos hídricos geralmente são elevados, no entanto, há custos de não se fazer a gestão, inclusive com desdobramentos, entre eles a escassez, e esta interfere causando prejuízos nas atividades econômicas (custo da escassez), especialmente na agrícola, que possui forte dependência da água para incremento em produtividade. Abordando a escassez e o custo da escassez na região agrícola da Bacia Hidrográfica do Rio Santa Maria, Mattiuzi et al (2019), demonstraram, no cenário de Alocação Atual de Água (situação atual da bacia) que o custo da escassez foi um total acumulado de quase R$ 2 bilhões em 15 anos. Na comparação com cenários em que há alocação econômica da água, o custo da escassez foi reduzido para R$ 0,47 bilhões com redução também da escassez para um terço.…”
Section: Cenáriounclassified
“…The irrigated agriculture marginal net benefit function was then derived from a previous hydro‐economic study in a neighboring region (Mattiuzi et al, 2019), which built a positive economic model calibrated to observed conditions with a PMP ( positive mathematical modeling ) approach (Howitt, 1995). The result is a function with net marginal values ranging from 0.01 to 0.08$/m 3 , which are close to those obtained in (Mattiuzi et al, 2019). As the irrigated agriculture sector grows, new users join the system with production conditions that are increasingly less favorable (e.g., further from the river, less favorable topography, and soil conditions).…”
Section: Applicationmentioning
confidence: 99%